Sistema de integração de técnicas de proteção de privacidade que permitem personalização - Grande, Robson Eduardo de (2006)
The interface implementation in e-commerce applications must consider two aspects: the privacy necessities of the user and the marketing utilization by the personalization application in services provided by sites in the Web. In this context, there are several mechanisms developed as to accomplish the data gathering as to bring to the user certain privacy level. Sites use since formularies in Web pages until techniques as clickstream, cookies and data mining to obtain information, to analyze them and to accomplish personalization. Current mechanisms for privacy protection are limited in their ability to provide privacy guarantees to data gathered on the Web, and some of them don t allow the data gathering by Web sites. The MASKS system manages the anonymity of its users and allows the implicit collecting of data. It neither provides security in the explicit gathering and nor allows the creation of browsing sessions via grouping of cookies into groups of different interests. Project 3P introduces a mechanism to keep users aware of privacy policies while they navigate Web sites. It adds low reliance to the implicit gathering. Here, we introduce a new system that combines an extension of MASKS system, an extension of P3P and an architecture of privacy certification. This combined system gathers the best qualities of each mechanism, and removes their limitations. The extended MASKS system includes sessions in the masking proxy to enable the creation of browsing sessions. The extended P3P adds information about the user benefits in disclosing his/her data to Web services. The privacy certificates guarantees the accomplishment of the policies stated by sites. Tests with users were carried out in order to compare and to evaluate the advantages of using this newly combined system. The results showed that the combined system provides users navigation with higher reliability. Thus, the implementation of this system proves useful for providing privacy during Web browsing, without impeding data gathering.